THE EXPERIENCE OF UNDERGRADUATE SAUDI ARABIAN INTERNATIONAL STUDENTS AT A CANADIAN UNIVERSITY - Alamri, Naif Ali (Journal of Educational and Psychological Sciences, 2018)
This study examined the experiences of undergraduate Saudi Arabian international students studying at a Canadian university. Considering the cultural, religious, and academic differences that the participants of this study experienced, this qualitative study highlights the personal and academic challenges that undergraduate Saudi Arabian international students encounter during their studies in Canada. By examining this group in interaction within ordinary settings, I expected to discern examples such as academic adjustments, social networks and events, and cultural themes. Data was gathered for this study by interviewing four Saudi Arabian students studying various undergraduate programs at one university in Canada. This study provides a wider understanding of the issues that Saudi Arabian international students encounter when they choose to come to pursue their university education in Canada. The findings of this study may have implications for higher education professionals and may add to the limited literature of Saudi Arabian international students in Canada. As well, it will contribute to the literature on cross-cultural education and international students’ adjustment issues.